2009
DOI: 10.1080/07373930802565954
|View full text |Cite
|
Sign up to set email alerts
|

Baking of Flat Bread in an Impingement Oven: Modeling and Optimization

Abstract: An artificial neural network (ANN) was developed to model the effect of baking parameters on the quality attributes of flat bread; i.e., crumb temperature, moisture content, surface color change and bread volume increase during baking process. As the hot air impinging jets were employed for baking, the baking control parameters were the jet temperature, the jet velocity, and the time elapsed from the beginning of the baking. The data used in the training of the network were acquired experimentally. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…ML‐based modeling is an exciting option to predict baking kinetics and control the quality of the product without much difficulty. Considering the benefits of ML‐based predictive modeling, recently researchers have attempted to apply ML in many areas of food baking such as the baking of biscuits/cookies (Broyart & Trystram, 2003; Isleroglu & Beyhan, 2020; Olawoye et al., 2020), milk cake (Emerald et al., 2020), bread (Banooni et al., 2009; Sablani et al., 2002), and soft cake (Goyal & Goyal, 2011).…”
Section: In Food Processing Applicationsmentioning
confidence: 99%
“…ML‐based modeling is an exciting option to predict baking kinetics and control the quality of the product without much difficulty. Considering the benefits of ML‐based predictive modeling, recently researchers have attempted to apply ML in many areas of food baking such as the baking of biscuits/cookies (Broyart & Trystram, 2003; Isleroglu & Beyhan, 2020; Olawoye et al., 2020), milk cake (Emerald et al., 2020), bread (Banooni et al., 2009; Sablani et al., 2002), and soft cake (Goyal & Goyal, 2011).…”
Section: In Food Processing Applicationsmentioning
confidence: 99%
“…A few studies have taken into account the effect of temperature on the viscosity of nanofluids. Yang et al [27] measured the viscosity of a nanofluid comprised of graphite nanoparticles at four different temperatures (35,43,50, and 70 • C). They showed that kinematic viscosity is decreased with raising the temperature.…”
Section: Advances In Mechanical Engineeringmentioning
confidence: 99%
“…This tool has been previously utilized in modeling and prediction of Stainless Steel Clad Bead [32], heat exchangers for cooling applications [33], and analysis on performance of heat pumps [34]. Neural network was also used in one earlier work by the authors of this article to predict the quality of bread in cooking process [35]. However, just a few studies have recently adopted this method in their estimations for nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Time and the volume of calculations can be significantly reduced by the application of this tool in CFD. Neural networks have been used in various fields of engineering . However, just a few studies have recently adopted this method for nanofluids .…”
Section: Introductionmentioning
confidence: 99%